Virtual Indication of the Torque for a Marine Gas Turbine - Niculescu, Filip; Vasile, Mirela Letitia; Balan, George; Săvescu, Adrian; Nicolae, Roxana (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Gas turbines are used in marine applications where high propulsion power is required compared to engine size and mass. In some cases, the torque and engine power developed cannot be measured with a special transducer implemented in applications or if there are indications, they need to be compared with the calculated torque indication. For this purpose, we developed in the engine control software application a mathematical model for calculating and displaying the torque and power developed by the engine. Through comparisons in the tests with the engine on the test bench, this mathematical model was refined. At this time the comparative sampled data can be used as a virtual indication of torque in cases where this is necessary.